Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13014-017-0789-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvage prostate re-irradiation using high-dose-rate brachytherapy or focal stereotactic body radiotherapy for local recurrence after definitive radiation therapy

Abstract: BackgroundOptimal management of locally recurrent prostate cancer after definitive radiation therapy is still challenging. With the development of highly accurate radiotherapy devices, prostate salvage re-irradiation might generate lower toxicity rates than classical salvage therapies. We retrospectively evaluated the toxicity and the feasibility of a prostate re-irradiation after definitive radiation therapy failure. Two modalities were investigated: high-dose-rate brachytherapy (HDRB) on whole prostate gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…Since toxicity our series was very low despite the inclusion of numerous patients with comorbidities, we do believe that BED >130 Gy should be considered in all patients undergoing salvage SBRT (re-EBRT). Higher doses were employed by some investigators15,17,20,21,23,24,26 still maintaining acceptable toxicity level and somehow higher tumor control when compared to our findings. We do believe that these somehow suboptimal tumor control might be explained both by inclusion of patients with aggressive disease (high PSA and Gleason score at the first diagnosis and at the diagnosis of recurrent cancer) and relatively low doses prescribed in our series.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Since toxicity our series was very low despite the inclusion of numerous patients with comorbidities, we do believe that BED >130 Gy should be considered in all patients undergoing salvage SBRT (re-EBRT). Higher doses were employed by some investigators15,17,20,21,23,24,26 still maintaining acceptable toxicity level and somehow higher tumor control when compared to our findings. We do believe that these somehow suboptimal tumor control might be explained both by inclusion of patients with aggressive disease (high PSA and Gleason score at the first diagnosis and at the diagnosis of recurrent cancer) and relatively low doses prescribed in our series.…”
supporting
confidence: 58%
“…The efficacy of salvage reirradiation for locally recurrent PCa has been evaluated by several investigations. [14][15][16][17][18][19][22][23][24][25][26][28][29][30][31][32][33][34] The first report on re-EBRT by Vavassori et al 15 including six cases treated by CyberKnife, showed the feasibility of reirradiation with an acceptable rate of acute and early chronic toxicity (median follow-up was 11.3 months). These preliminary findings were then confirmed by the successive series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent systematic review on focal salvage therapy for radio‐recurrent PCa, the 5‐year biochemical disease‐free survival rate was 46.5–54.5% . Feasibility trials have been performed with HIFU, cryosurgery, iodine‐125 brachytherapy and HDR brachytherapy . For whole‐gland salvage HIFU and cryosurgery, biochemical failure occurred in 3–79% of patients, and rates of preserved urinary continence and potency ranged from 10% to 93% and 15% to 56%, respectively .…”
Section: Introductionmentioning
confidence: 99%